2007
DOI: 10.1590/s0100-29452007000300038
|View full text |Cite
|
Sign up to set email alerts
|

Características físicas e acúmulo de nutrientes pelos cachos de 'niagara rosada' em vinhedos na região de Jundiaí

Abstract: RESUMO-Este trabalho teve por objetivo realizar um levantamento em 40 vinhedos de 'Niagara Rosada' nos municípios de Jundiaí e Louveira-SP, sendo metade sobre o porta-enxerto 'Ripária do Traviú' e outra sobre o 'IAC 766'. Determinaram-se, em cada vinhedo, a produtividade, a duração do ciclo, o número de cachos e de ramos produtivos por planta, as características físicas dos cachos e bagas, e o acúmulo de nutrientes pelos cachos. Avaliaram-se nos cachos amostrados a massa da matéria fresca, o comprimento e a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 3 publications
1
8
0
5
Order By: Relevance
“…As características físicas e o acúmulo de nutrientes nos cachos da cultivar Niágara Rosada sobre os porta-enxertos 'Ripária do Traviú' e 'IAC 766' foram avaliados em cultivos na região de Jundiaí, SP (Tecchio et al, 2007). Os autores observaram resultados semelhantes na produtividade e nas características físicas dos cachos, entretanto houve diferenças no teor de nutrientes nas folhas e no acúmulo de nutrientes pelos cachos.…”
unclassified
“…As características físicas e o acúmulo de nutrientes nos cachos da cultivar Niágara Rosada sobre os porta-enxertos 'Ripária do Traviú' e 'IAC 766' foram avaliados em cultivos na região de Jundiaí, SP (Tecchio et al, 2007). Os autores observaram resultados semelhantes na produtividade e nas características físicas dos cachos, entretanto houve diferenças no teor de nutrientes nas folhas e no acúmulo de nutrientes pelos cachos.…”
unclassified
“…The amounts of N, P, K, Ca and Mg were, respectively, of 64.9, 19.0, 156.9, 45.8 and 12.66 kg ha -1 when grafted on 'Paulsen 1103';and 112.8, 29.3, 260.8, 82.3 and 26.0 kg ha -1 when grafted on 'VR 043-43'. During a nutritional survey in Jundiai, state of Sao Paulo, Tecchio et al (2007) concluded that 'Niagara Rosada' grafted on '106-8 Mgt' rootstocks presented high levels of P, Fe and Zn in the clusters, whereas on 'IAC 766' rootstocks had a high level of Mn. On both rootstocks, 'Niagara Rosada' presented the following descending order of nutrient accumulation within the clusters: K > N > P > Ca > S > Mg > B > Fe > Mn > Cu > Zn.…”
Section: Introductionmentioning
confidence: 99%
“…Zoological nomenclature imposes Latin terminations, hence supposes Latinization of Greek (and other non-Latin) elements. Dactylosphaera is therefore the spelling more in the spirit of the system, although per ICZN Article 32.5.1 (International Commission on Zoological Nomenclature 1999), “incorrect transliteration or Latinization … are not to be considered inadvertent errors.” In addition to these two official spellings, other authors have used every possible combination of c/k, u/y and ae/ai to refer to the grape phylloxeran, giving Dactulosphaera (e.g., Kleeburg and Hummel 2001), Dactulosphaira (e.g., Fahrentrapp et al 2015), Dactylosphaira (e.g., Alleweldt et al 1991), Daktulosphaera (e.g., Loxdale 2008), Daktylosphaera (e.g., Tecchio et al 2007), and Daktylosphaira (e.g., Torregrossa et al 1997). …”
Section: Introductionmentioning
confidence: 99%